Matrix-bound EGF promotes malignant phenotypes of breast cancer organoids in the biomimetic ECM of alginate - Xue-Yu Chen; Meng-Yuan Wang; Xin Shu; Jun Li; Ruizhi Tang; Xi-Qiu Liu (Materials Today Bio)
As multiple malignant phenotypes appear during cancer progression, it is essential to recognize the possible mechanisms from original to metastatic states. However, both two-dimensional monolayer cell culture and in vivo animal models have their inherent limitations, such as lack of proper cell-ECM interactions and uncontrollable variables. By their heterogeneous simulation of tumor processes, 3D organoids can better recapitulate real tumor characteristics and more realistic responses to distinct factors. Herein, this study was designed to establish in vitro 3D breast cancer organoid models in the recreating tumor-stroma niche by using alginate cryogels to mimic the porous ECM, especially to introduce the controlled release of matrix-bound growth factor EGF (83 % positive in human breast cancers). The matrix-bound EGF in the biomimetic ECM promoted malignant phenotypes of breast cancer organoids in proliferation, migration, epithelial-mesenchymal transition, apoptosis and drug resistance, in accordance with clinical evidence. The multi-omics analyses combined with molecular biological experiments revealed both cytokine-cytokine receptor interaction and ECM-receptor interaction functioned to activate PI3K-AKT pathways, to stimulate tumor-promoting cytokines (eg., IL18, IL33, GDF-15), to promote gene expression of ECM components (eg., FN1) and metabolic enzymes (eg., GOT2), and finally to reprogram breast cancer energy metabolism. This system would represent a new paradigm of cancer progression studies using in vitro 3D organoids in a biomimetic ECM, in order to develop novel therapeutic strategies and evaluate preclinical treatments.